2017
DOI: 10.1038/s41598-017-06086-2
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α regulates glioma chemosensitivity through the transformation between differentiation and dedifferentiation in various oxygen levels

Abstract: Chemotherapy plays a significant role in glioma treatment; however, it has limited effectiveness in extending the life expectancies of glioma patients. Traditional studies have attributed this lack of efficacy to glioma stem cells (GSCs) and their high resistance to chemotherapy, and hypoxia worsens this issue. In contrast, hyperoxia effectively alleviates hypoxia in glioma and sensitizes glioma cells to chemotherapy. In a summary of traditional studies, the majority of researchers overlooked the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Previous reporting demonstrated that Hypoxia-inducible factors (HIFs) are critical for maintenance of the BTIC niche and that HIF-1α (HIF1A) can directly modulate EZH2 expression via promoter binding 30,31 . We have shown that TMZ therapy increases the BTIC frequency in a HIF dependent manner 20,32 . Now we show that the TMZ-mediated increase in HIF1A is specific to the CD133+ BTIC compartment…”
Section: Ezh2 Expression Is Increased In the Btic Compartment During mentioning
confidence: 86%
See 1 more Smart Citation
“…Previous reporting demonstrated that Hypoxia-inducible factors (HIFs) are critical for maintenance of the BTIC niche and that HIF-1α (HIF1A) can directly modulate EZH2 expression via promoter binding 30,31 . We have shown that TMZ therapy increases the BTIC frequency in a HIF dependent manner 20,32 . Now we show that the TMZ-mediated increase in HIF1A is specific to the CD133+ BTIC compartment…”
Section: Ezh2 Expression Is Increased In the Btic Compartment During mentioning
confidence: 86%
“…A canonical driver of context-dependent epigenetic plasticity is the Polycomb Repressor Complex (PRC) and its catalytic subunit Enhancer of Zeste Homologue 2 (EZH2). The PRC2/EZH2 complex not only required for different neurodevelopmental processes but also associated with disease pathogenesis including GBM [13][14][15][16][17][18][19][20] . Tumor cells can also adapt to treatment metabolically by rapidly altering core metabolic pathway activity 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…We also identified that HIF-1α can be upregulated in TNBC cells after short-term hyperoxia exposure. There is a vast body of literature demonstrating that HIF-1α increases in hypoxia while in hyperoxic regimens usually decreases [17,18]. However, in skeletal muscle cells under high oxygen concentrations (42%), the amount of HSP90-HIF-1α complex is increased and suggests that HSP90 stabilizes cytoplasmic HIF-1α under high oxygen levels [39].…”
Section: Angiogenesis Is Enhanced By 6 H O 2 Exposure In Triple Negatmentioning
confidence: 99%
“…In cancer BDNF has been shown to play a role in proliferation, invasion and metastasis in central nervous system, mammary, ovarian, pancreatic and uterine neoplasms [13][14][15][16]. BDNF promotes angiogenesis by increasing VEGFR expression through HIF-1α [17].Small levels of ROS will induce insufficient BDNF expression, while high levels of ROS will induce extended BDNF stimulation leading to epithelial mesenchymal transition (EMT) and angiogenesis. EMT induces new cancer stem cell formation that may be responsible for cancer recurrence.…”
mentioning
confidence: 99%
See 1 more Smart Citation